PENDAMPINGAN DESA SEHAT MELALUI PENCEGAHAN STUNTING BERBASIS EDUKASI POLA ASUH KELUARGA DAN JAJANAN SEHAT - Nuzulan, Moch Aji Zulfan; Salsabila, Annisa; Nisa F, Muslimatun; Dyahredaya, Galuh; Saputri, Ginanjar Zukhruf; Utami, Nurul Putri (Jurnal Abdi Insani, 2024)
The prevalence of stunting is still quite high in Indonesia, and is a global health problem. One of the factors that causes stunting is a lack of knowledge regarding parenting patterns and healthy snacks which indirectly causes malnutrition and infectious diseases in children. This community service aims to find out family parenting patterns and healthy snacks implemented in Hargotirto Village, Kokap, Kulonprogo. Method: Method of implementing community service programs through interactive education (lectures) and questions and answers. The activity was attended by toddler health posyandu cadres in Hargotirto Village, Kulonprogo. Evaluation of educational interventions is seen from participants' knowledge which is measured in the pre-test and post-test activities through structured questionnaires and expert validation has been carried out. The level of knowledge of participants showed an increase after the education on stunting prevention. The results of the average score for community knowledge regarding parenting increased from an average score of 19.4 to 20.65. Meanwhile, the average score for children's knowledge of healthy snacks increased from 20.63 to 26.3 after education. Stunting prevention assistance activities have a positive impact on increasing health cadres' knowledge regarding parenting patterns and healthy snacks. It is hoped that parents will be able to implement good parenting patterns, including balanced nutritional management for children, to prevent stunting